The Role of Mental Health in Multiple Exclusion Homelessness. Issue 3 (29th July 2022) - Pattison, Ben; McCarthy, Lindsey
Abstract : Development of effective policy responding to recent increases in rough sleeping in England requires an understanding of the needs of people experiencing homelessness. Research on multiple exclusion homelessness (MEH) should be central to policy development as it highlights the interactions between 'homelessness' and 'deep social exclusion'. This article focuses on the nexus between mental health and homelessness within MEH. Mixed methods findings from Nottingham, England, are used to investigate the role of mental ill-health in the pathways into MEH. This included a survey of the mental health needs of homeless people and 'homeless pathway' interviews. Survey results demonstrated high levels of diagnosed and self-reported mental health issues. Interviews highlighted that mental ill-health and homelessness were closely associated with adverse life experiences and could not be viewed in isolation from them. The article contributes further insight on the specificities of mental health issues, their temporal ordering, and interrelationship with homelessness experiences.